Automated diagnosis and treatment by lasers employing Raman spectroscopy and catheter with optical fibers. Issue 3 (2011) - Lázaro, João Carlos; de Paula, Alderico Rodrigues; Moreira, Leonardo Marmo; Lyon, Juliana Pereira; Pacheco, Marcos Tadeu T.; de Lima, Carlos José
Abstract : Raman spectroscopy is considered a very powerful tool for biochemical characterization, especially regarding biological samples. This technique allows the diagnosis of several diseases, such as cancer and atherosclerosis. In this context, the non invasive or minimally invasive character of the spectroscopic resources is an auspicious clinical advancement when compared with conventional procedures, which are associated to significant trauma and possible decrease in the quality of life of patients. Recently, the use of catheter with optical fibers associated to Raman spectroscopy has significantly minimized the invasive character of several clinical procedures. It is important to notice that this optical sensor already presents flexibility due to the employment of optical fibers to applications of lasers. Nowadays, this kind of device possesses autonomy of use and can be coupled to an optic fiber in order to permit the treatment with lasers. In this way, it is possible to develop an electronic automated optic system that achieves a diagnosis through catheter with optic fiber connected to a Raman spectrometer in order to analyze a certain organ and, considering the diagnosis obtained, to develop the adequate optical treatment can be automatically selected and applied to the respective organ. In the present work, the structure of this device will be presented with the more suitable optical techniques available to the laboratories. The minimum intervals of time involving each step of the sequence are evaluated and the efficiency of the spectroscopic system is discussed in details in agreement with the literature.